Simulation of nonequilibrium hypersonic flows - Riedel, Uwe; Maas, Ulrich; Warnatz, Jürgen (Computers & fluids, 1993)
Simulation of hypersonic reacting flows is a challenging task, due not only to the large variety of applications (e.g. reentry problems of space vehicles or supersonic combustion etc.) but also to the fact that a large amount of computational and numerical efforts have to be made in order to overcome the difficulties in the numerical solution of the governing Navier Stokes equations. Whereas very often mathematical modelling is simplified by neglecting second-order effects like molecular transport, thus solving the Euler equations, several interesting phenomena such as gas-surface interactions require the solution of the full set of Navier-Stokes equations. The algorithm presented here is based on a fully conservative formulation of the conservation equations and uses a first-order flux-splitting scheme. The large system of ordinary differential and algebraic equations resulting from the spatial discretization is solved by a time-accurate implicit extrapolation method. In comparing two different nonequilibrium reaction schemes we show that finite rate chemistry has a strong influence on the computed flowfield, e.g. the maximum temperature in the shock wave or the species concentrations.